2015
DOI: 10.1097/nne.0000000000000174
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an International Cooperative Education Experience for Undergraduate Nursing Students

Abstract: A qualitative study was conducted to identify the outcomes of international cooperative education in nursing. Seventeen alumni who completed 19 cooperative work experiences were interviewed. International cooperative experiences support learning about culture and contribute to personal and professional development. Outcomes included increased maturation, confidence, and flexibility; elevated political and global awareness; and ability to create effective relationships with culturally diverse patients and cowor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…19 The students in a study by Hoffart et al, which focused on cooperative (clinical) education experiences, also reported personal growth-oriented outcomes such as maturation, confidence and resilience development, and open-mindedness. 20…”
Section: Literature Review: Study Abroad In Nursing Educationmentioning
confidence: 99%
“…19 The students in a study by Hoffart et al, which focused on cooperative (clinical) education experiences, also reported personal growth-oriented outcomes such as maturation, confidence and resilience development, and open-mindedness. 20…”
Section: Literature Review: Study Abroad In Nursing Educationmentioning
confidence: 99%
“…According to Smith and Macintosh [54], the length of time of the immersion experience can also affect cultural competency development; this is not to say that a one-day cultural immersive program will not enable such development, but it may impact the proficiency level, as students may not be exposed to different influences that may impact the health of the target population Contrary to this thought, Philips et al [55] indicated in their research that there was no agreement on the optimum approach or requirements to prepare for an immersion experience, nor did there appear to be a conventional timeframe for preparing for an immersion experience. Hoffart et al [56] stated that the duration of time might not impact cultural competency development, but a time is needed for the student to reflect on their experiences to solidify their gains in cultural competency, which was achieved after the cultural immersion program for students who engaged with host families in this study.…”
Section: Discussionmentioning
confidence: 80%